Structure and Chemical Reactivity of Y‐Stabilized ZrO2 Surfaces: Importance for the Water‐Gas Shift Reaction - Chen, Shuang; Pleßow, Philipp N.; Yu, Zairan; Sauter, Eric; Caulfield, Lachlan; Nefedov, Alexei; Studt, Felix; Wang, Yuemin; Wöll, Christof (Angewandte Chemie International Edition, 2024)
The surface structure and chemical properties of Y‐stabilized zirconia (YSZ) have been subjects of intense debate over the past three decades. However, a thorough understanding of chemical processes occurring at YSZ powders faces significant challenges due to the absence of reliable reference data acquired for well‐controlled model systems. Here, we present results from polarization‐resolved infrared reflection absorption spectroscopy (IRRAS) obtained for differently oriented, Y‐doped ZrO2 single‐crystal surfaces after exposure to CO and D2O. The IRRAS data reveal that the polar YSZ(100) surface undergoes reconstruction, characterized by an unusual, red‐shifted CO band at 2132 cm−1. Density functional theory calculations allowed to relate this unexpected observation to under‐coordinated Zr4+ cations in the vicinity of doping‐induced O vacancies. This reconstruction leads to a strongly increased chemical reactivity and water spontaneously dissociates on YSZ(100). The latter, which is an important requirement for catalysing the water‐gas‐shift (WGS) reaction, is absent for YSZ(111), where only associative adsorption was observed. Together with a novel analysis Scheme these reference data allowed for an operando characterisation of YSZ powders using DRIFTS (diffuse reflectance infrared Fourier transform spectroscopy). These findings facilitate rational design and tuning of YSZ‐based powder materials for catalytic applications, in particular CO oxidation and the WGS reaction. We present a systematic IR spectroscopic study on Y‐stabilized ZrO2 (YSZ) in the form of both well‐defined single‐crystals (polarization‐resolved IRRAS) and nanoparticles (in situ IR transmission, high‐pressure DRIFTS) with a special focus on the polar YSZ(100) surface and its interactions with CO and D2O. The IR results in conjunction with DFT calculations demonstrate that this surface is characterized by low‐coordinated Zr4+ cations in the presence of O vacancies generated by Y3+‐doping, showing superior activity for low‐temperature water dissociation.